2016
DOI: 10.1007/s12517-016-2324-y
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal patterns of climate variables in Iraq

Abstract: Temporal and spatial changes in Iraq total precipitations, maximum and minimum temperatures in the period of 1980-2011 are analyzed using 28 meteorological stations data distributed throughout the country. The Mann-Kendall and Spearman's Rho test statistics for annual and seasonal Kendall and Sen's T tests for monthly total precipitation and temperature series are calculated and plotted on maps to display any spatial trend patterns. Serial correlation structure in the data series and homogeneity of trends in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(9 citation statements)
references
References 23 publications
0
9
0
Order By: Relevance
“…Among the investigated aridity indices, Im index showed a maximum decreasing trend of aridity indices with a slope of −0.32 to −0.02 (mm/mm)/year, while AIu had a minimum decreasing trend of aridity indices for all stations with a decrease of −0.006 to −0.0002 (mm/mm)/year. Actually, the maximum decreasing slope in total precipitation data was also detected in Khanaqin station (Mahmood Agha and Şarlak 2016). This emphasizes that the most sensible parameters to aridity in this region is precipitation.…”
Section: Resultsmentioning
confidence: 64%
“…Among the investigated aridity indices, Im index showed a maximum decreasing trend of aridity indices with a slope of −0.32 to −0.02 (mm/mm)/year, while AIu had a minimum decreasing trend of aridity indices for all stations with a decrease of −0.006 to −0.0002 (mm/mm)/year. Actually, the maximum decreasing slope in total precipitation data was also detected in Khanaqin station (Mahmood Agha and Şarlak 2016). This emphasizes that the most sensible parameters to aridity in this region is precipitation.…”
Section: Resultsmentioning
confidence: 64%
“…A more comprehensive statistical analysis by Salman et al (2018b) suggested unidirectional trends in rainfall and rainfall-related extremes in Iraq. Agha and Şarlak (2016) analyzed climate variables observed at 28 Iraqi meteorological stations in the period of 1980-2011 and concluded that such climatic impacts were spatially uniform. However, Salman et al (2018a) selected an ensemble of general circulation models to project higher increases in temperatures in the north and northeast of Iraq in the 21st century.…”
Section: Overview Of the Study Sitementioning
confidence: 99%
“…The scarcity of conventional electrical energy sources and costs encouraged researchers to examine the air conditioner general functional design and applications and acquiring new methods and processes to achieve suitable conditions in buildings by ordinary means. During the summer season in Iraq, the weather condition is very hot and dry, while the outdoor temperature sometimes surpasses 50 °C [1,2]. Iraq experiences insufficiency in production in electrical power and several other challenges to meet the increasing demand for electrical power.…”
Section: Introductionmentioning
confidence: 99%